TikTok and Political Communication: The Latest Frontier of Politainment? A Case Study - Cervi, Laura (2023)
TikTok is without any doubt the most popular social media among Gen Zers. Originally born as a lip-syncing app, it can be exploited in different ways; as such, it represents a new fertile space for political communication. In this vein, previous studies have shown that politicians all over the planet are joining the platform as a tool to connect with younger audiences. This study examines the use of TikTok in the last presidential elections in Peru. Following an affordance-based approach, we analyze all the TikToks published by the main candidates (Pedro Castillo, Keiko Fujimori, Rafael Lopez Aliaga, Hernando de Soto, and George Forsyth) during the electoral campaign, to understand if and how candidates have integrated this platform as part of their electoral strategy and what kind of content they publish and share. Through a content analysis that combines quantitative and qualitative elements, we demonstrate that, although all the analyzed politicians have opened TikTok accounts, they do not seem to take full advantage of the platform’s affordances displaying a top-down communication style with almost no deliberative nor participative intentions. Political issues are almost absent since the platform is mostly used to display their personal life and enhance their political persona, with most of the content displaying a clear entertaining dimension. Some differences are discussed but, in general, results reveal that Peruvian candidates use TikTok almost uniquely for politainment.